Production of succinic acid from liquid hot water hydrolysate derived from Quercus mongolica. (July 2021) - Kim, Jong-Hwa; Choi, June-Ho; Kim, Jong-Chan; Jang, Soo-Kyeong; Kwak, Hyo Won; Koo, Bonwook; Choi, In-Gyu
Abstract: The main purpose of this study was to produce succinic acid from hemicellulose in lignocellulosic biomass by successive process without purification as a biorefinery concept. Liquid hot water (LHW) treatment was conducted to extract water soluble hemicelluloses from Quercus mongolica to produce furfural from lignocellulosic biomass. Additional acid catalyzed dehydration was conducted to liquid hydrolysate from LHW treatment for furfural production. At 170 °C of reaction temperature, 42% of furfural yield was achieved from pentose in liquid hydrolysate. This Acid treated liquor (ATL) was treated with hydrogen peroxide to oxidize furfural to C4 dicarboxylic acid such as succinic or maleic acid. Main product was succinic acid which is produced by oxidation of furfural, and minor amount of maleic acid was produced via oxidation. The xylose was degraded to furfural and then oxidized to succinic acid, while acid soluble lignin inhibited succinic acid production by reacting with intermediates of succinic acid. This results indicated that hemicellulose rich liquid hydrolysate has potential to source for succinic acid without further purification. Highlights: Liquid hot water treatment was conducted to extract hemicellulose from biomass. Furfural was produced via acid catalyzed dehydration of hemicellulose. Sequential addition of hydrogen peroxide oxidized furfural to succinic acid. Xylose in liquid was oxidized to succinic acid. Acid soluble lignin tended to react with intermediates of succinic acid.